Teknologi Edible Coating untuk Memperpanjang Masa Simpan Tomat di Desa Lingga, Kecamatan Simpang Empat, Kabupaten Karo - Healthy Aldriany Prasetyo; Angga Ade Sahfitra (Pelita Masyarakat, 2022)
Community Service The Stimulus Scheme (PKMS) is implemented as part of the Tri Dharma of Higher Education which aims to assist the community in increasing knowledge and skills in the field of post-harvest handling of tomatoes. The implementation of the activity lasted for 3 days with the location in Lingga Village, Simpang Empat District, Karo Regency. The service activity was carried out using an extension method (Focus Group Discussion = FGD) with material on the physiological process of tomatoes and demonstration of stearin-based edible coating applications. The results of the evaluation showed that there was an increase in participants' knowledge of the physiological processes of tomatoes. Increased knowledge is expressed by giving correct answers to the questions listed on the questionnaire sheet by 85.3%. The skills of the participants also experienced an increase which was marked by the ability to make edible coating formulations, and being able to apply edible coatings to tomatoes correctly.